Analysis of causes of maternal mortality in tertiary care center, 11 years study - Saravade, Vandana R.; Ansari, Munira; Shinde, Ganesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Objectives to study the causes of maternal mortality and the complications leading to maternal death. Methods: A retrospective study of hospital records and death summaries of all maternal death over a period of 11 years from January 2008 to December 2018 was carried out at tertiary care hospital, Mumbai. Results: There were a total of 459 maternal death out of 36930 live birth giving maternal mortality rate mean maternal mortality ratio (MMR) of 1242 per 100000 live births. Unregistered and late referral account for maternal death. The majority of women were in 21-30 years age group in 20 to less than 37 weeks of pregnancy. The commonest cause of death was due to hepatitis infection 129 (28.1%), sepsis 52 (11.32%), PIH including eclampsia 46 (10.02%), cardiovascular diseases 33 (7.18%), haemorrhage 31 (6.75%), Kochs 31 (6.75%) and respiratory diseases 22 (4.79%). Conclusions: Maternal mortality can be reduced by identifying causes which are preventable and giving timely treatment.